Holistic Character Education Strategy Based on Islamic Values at Darussalam Kalibakung Junior High School - Imamudin Imamudin; Abdul Khobir (Jurnal Paradigma, 2026)
Abstract This study is motivated by the limited effectiveness of character education in schools, which tends to prioritize academic-cognitive achievement while neglecting moral and spiritual development. This research aims to analyze the strategies, forms of implementation, and urgency of holistic character education based on Islamic Religious Education at SMP Darussalam Kalibakung, Tegal Regency. The study employs a descriptive qualitative approach with a case study design. Data were collected through literature review and documentation analysis of institutional school documents, including vision and mission statements, curriculum design, school regulations, and religious habituation programs. Data analysis was conducted through thematic categorization, contextual interpretation, and analytical synthesis between theoretical frameworks of holistic and Islamic character education and their practical implementation. The findings indicate that holistic character education at SMP Darussalam Kalibakung is implemented in an integrated manner through curriculum integration, school culture, religious habituation, and teacher role modeling. This approach shows positive implications for strengthening the internalization of Islamic values such as honesty, discipline, responsibility, empathy, and social awareness, while also contributing to improved learning quality and students’ holistic development. Abstrak Penelitian ini dilatarbelakangi oleh belum optimalnya capaian pendidikan karakter di sekolah yang masih didominasi oleh pendekatan akademik-kognitif dan kurang menyentuh pengembangan nilai moral dan spiritual peserta didik. Dalam konteks tersebut, penelitian ini bertujuan untuk menganalisis strategi, bentuk implementasi, serta urgensi pendidikan karakter holistik berbasis Pendidikan Agama Islam di SMP Darussalam Kalibakung, Kabupaten Tegal. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan desain studi kasus. Data diperoleh melalui studi literatur dan dokumentasi terhadap dokumen institusional sekolah, seperti visi-misi, kurikulum, tata tertib, serta program pembiasaan religius dan budaya sekolah. Analisis data dilakukan melalui pengelompokan tema, interpretasi kontekstual, dan sintesis antara kerangka teoretis pendidikan karakter holistik berbasis nilai Islami dan praktik implementatif di sekolah. Hasil penelitian menunjukkan bahwa pendidikan karakter holistik di SMP Darussalam Kalibakung diimplementasikan secara terintegrasi melalui kurikulum, budaya sekolah, pembiasaan religius, serta keteladanan guru. Strategi ini berimplikasi positif terhadap penguatan internalisasi nilai-nilai Islami, seperti kejujuran, disiplin, tanggung jawab, empati, dan kepedulian sosial, serta berkontribusi pada peningkatan kualitas pembelajaran dan perkembangan peserta didik secara menyeluruh.